Generation blend : managing across the technology age gap - Salkowitz, Rob, 1967- (Microsoft executive leadership series., 2008)
Generation Blend explores the origins, characteristics, and implications of generational attitudes of people toward information technology and showcases two innovative approaches to bridging the generational-digital divide. It discusses approaches to technology that empower people of all ages to contribute their talent, knowledge, and experience to the workplace, and offers ways to foster productive intergenerational dialogue around business and technology issues.